2013
DOI: 10.1002/lary.24419
|View full text |Cite
|
Sign up to set email alerts
|

A pain in the neck

Abstract: A lateralized pain in the neck is a common symptom encountered by the otolaryngologist. This complaint, frequently caused by lateral thyrohyoid ligament syndrome, is often misdiagnosed. The pathophysiology of this syndrome may relate to overuse and inflammation. [change made here after initial online publication]. Typically, patients present with chronic unilateral neck pain often associated with odynophagia. The point of maximum tenderness localizes over the axis of the lateral thyrohyoid ligament. We present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…38 Inflammation of this ligament can be caused by frequent coughing, high vocal demands, and strenuous neck movement. 39 Interestingly, these symptoms all parallel common complaints in patients with pMTD. The close proximity of laryngeal sensory afference in the area of the anterior neck that had the most significant movement pattern differences between groups is also of interest considering we previously found that paralaryngeal sensation may play a role in pMTD 29 and that pMTD can manifest as Irritable Larynx Syndrome.…”
Section: Greater Movement Displacement In the Thyrohyoid Space In The...mentioning
confidence: 89%
See 1 more Smart Citation
“…38 Inflammation of this ligament can be caused by frequent coughing, high vocal demands, and strenuous neck movement. 39 Interestingly, these symptoms all parallel common complaints in patients with pMTD. The close proximity of laryngeal sensory afference in the area of the anterior neck that had the most significant movement pattern differences between groups is also of interest considering we previously found that paralaryngeal sensation may play a role in pMTD 29 and that pMTD can manifest as Irritable Larynx Syndrome.…”
Section: Greater Movement Displacement In the Thyrohyoid Space In The...mentioning
confidence: 89%
“…Pain in the lateral thyrohyoid ligament can cause unilateral neck tenderness with touch, odynophonia and odynophagia, and globus and foreign body sensation 38 . Inflammation of this ligament can be caused by frequent coughing, high vocal demands, and strenuous neck movement 39 …”
Section: Discussionmentioning
confidence: 99%
“…Patients with lateral thyrohyoid ligament syndrome present with lateralized cervical pain (which can last >12 months) and odynophagia, with characteristic tenderness over the lateral thyrohyoid ligament axis, evidenced by wincing and withdrawal on palpation. A combination of steroid injections and local anesthetics is a viable and effective therapeutic option that reduces pain [ 13 ].…”
Section: Thyroid Cartilage Fracture and Thyrohyoid Ligament Syndromementioning
confidence: 99%
“…The thyrohyoid syndrome presents as such and is a little-known inflammatory condition of the lateral thyrohyoid ligament and nearby tissues. It is distinctive from the well-known hyoid- or eagle syndrome [ 1 ]. We chose to present this little-known condition as a case report to promote awareness among health care workers with the goal of increasing correct diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In regards to its pathogenesis, irritative inflammation of the ligamentous, cartilaginous or bursa-related anatomical structures of the thyrohyoid region is believed to be the cause of the symptoms and can be triggered by overuse or factors such as a cough, voice abuse or strenuous neck and upper limb movements [ 1 ]. The first mention of this syndrome in the literature cannot be defined because imprecise and unstandardized nomenclature has been used in the past.…”
Section: Introductionmentioning
confidence: 99%